Dominant Vibrio cholerae phage exhibits lysis inhibition sensitive to disruption by a defensive phage satellite - Stephanie G Hays; Kimberley D Seed (eLife, 2020)
Bacteria, bacteriophages that prey upon them, and mobile genetic elements (MGEs) compete in dynamic environments, evolving strategies to sense the milieu. The first discovered environmental sensing by phages, lysis inhibition, has only been characterized and studied in the limited context of T-even coliphages. Here, we discover lysis inhibition in the etiological agent of the diarrheal disease cholera, Vibrio cholerae, infected by ICP1, a phage ubiquitous in clinical samples. This work identifies the ICP1-encoded holin, teaA, and antiholin, arrA, that mediate lysis inhibition. Further, we show that an MGE, the defensive phage satellite PLE, collapses lysis inhibition. Through lysis inhibition disruption a conserved PLE protein, LidI, is sufficient to limit the phage produced from infection, bottlenecking ICP1. These studies link a novel incarnation of the classic lysis inhibition phenomenon with conserved defensive function of a phage satellite in a disease context, highlighting the importance of lysis timing during infection and parasitization.